2011
DOI: 10.1200/jco.2010.30.2729
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Bevacizumab Plus Temozolomide During and After Radiation Therapy for Patients With Newly Diagnosed Glioblastoma Multiforme

Abstract: Purpose This open-label, prospective, multicenter single-arm phase II study combined bevacizumab (BV) with radiation therapy (RT) and temozolomide (TMZ) for the treatment of newly diagnosed glioblastoma (GBM). The objectives were to determine the efficacy of this treatment combination and the associated toxicity. Patients and Methods Seventy patients with newly diagnosed GBM were enrolled between August 2006 and November 2008. Patients received standard RT starting within 3 to 6 weeks after surgery with concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
330
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 424 publications
(344 citation statements)
references
References 15 publications
10
330
1
3
Order By: Relevance
“…Other prognostic markers for glioblastoma (e.g., surgery status, Karnofsky performance status, age, and recursive partitioning analysis class) were also not predictive of survival, findings that were consistent with those in previous studies. 21 The addition of bevacizumab to standard radiotherapy-temozolomide therapy as first-line treatment for glioblastoma was also investigated in the phase 3, randomized, placebo-controlled Radiation Therapy Oncology Group (RTOG)-0825 study. That study showed a similar trend toward improvement in progression-free survival (hazard ratio, 0.79; 95% CI, 0.66 to 0.94; P = 0.007), with a 3.4-month extension of progression-free survival, although the difference was not significant according to the prespecified alpha level (P<0.004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other prognostic markers for glioblastoma (e.g., surgery status, Karnofsky performance status, age, and recursive partitioning analysis class) were also not predictive of survival, findings that were consistent with those in previous studies. 21 The addition of bevacizumab to standard radiotherapy-temozolomide therapy as first-line treatment for glioblastoma was also investigated in the phase 3, randomized, placebo-controlled Radiation Therapy Oncology Group (RTOG)-0825 study. That study showed a similar trend toward improvement in progression-free survival (hazard ratio, 0.79; 95% CI, 0.66 to 0.94; P = 0.007), with a 3.4-month extension of progression-free survival, although the difference was not significant according to the prespecified alpha level (P<0.004).…”
Section: Discussionmentioning
confidence: 99%
“…16 The results of phase 1/2 studies support a role for the anti-VEGF-A molecule bevacizumab in recurrent and newly diagnosed glioblastoma. [17][18][19][20][21][22] We report the results of a phase 3 trial of bevacizumab plus radiotherapy-temozolomide as compared with placebo plus radiotherapytemozolomide in patients with newly diagnosed glioblastoma.…”
mentioning
confidence: 99%
“…Recently, the antiangiogenic drug bevacizumab (Avastin), a monoclonal antibody to VEGF, was approved in the United States for patients with recurrent GBM. Bevacizumab improves progression-free survival in GBM, associated with reduced steroid use, but confers little or no improvement in overall survival (4,5). Most targeted therapies to date are directed against druggable oncogenes identified through genomic profiling.…”
mentioning
confidence: 99%
“…GBMs are highly vascularized tumors and bevacizumab therapy may extend survival in some recurrent patients (Zuniga et al, 2009). To date, clinical studies that have assessed the benefit of adding bevacizumab to standard therapy in primary GBM have been less impressive (Lai et al, 2011). However, one study found that combining therapies against endothelial cells and pericytes can result in a synergistic antitumor effect (Bergers et al, 2003) supporting the concept that the use of many drugs directed toward different molecular targets can achieve optimal treatment response.…”
Section: Bevacizumabmentioning
confidence: 99%